Legislative Deferrals : - Lovell, George I (Cambridge University Press, 2003)
United States judges are criticized for making law when they should be following the laws made by elected officials. This book argues that much of the blame for judicial policymaking lies with elected officials. Legislators sometimes deliberately allow judges to make policy decisions because they want to avoid blame for making difficult choices. To demonstrate the importance of legislative deference, this study reexamines dramatic confrontations between Congress and the Supreme Court over labor policy in the early twentieth century.